The Turkish version of the National Eye Institute Refractive Error Quality of Life Instrument: translation, validity and reliability - TOKER, AYŞE EBRU; ERASLAN, MUHSİN (SPRINGER, 2008)
Purpose To translate the original 42-item National Eye Institute Refractive Error Quality of Life Questionnaire (NEI-RQL-42) into Turkish and to investigate its validity and reliability. Methods The linguistic translation followed the international guidelines of forward and backward translation. Ninety-five consecutive subjects (37 myopes, 18 hyperopes and 40 emmetropes) who had a visual acuity of 0.8 or better in the worse eye completed the NEI-RQL-42 and the Turkish version of the 25-item National Eye Institute Visual Functioning Questionnaire (NEI-VFQ-25). Eighty patients completed the NEI-RQL-42 for a second time within 2 weeks. Psychometric evaluation of the Turkish NEI-RQL-42 involved the assessment of internal consistency, test-retest reliability, convergent and known-groups validity. Results Internal consistency was generally high (Cronbach's alpha = 0.83-0.95), with the exception of three subscales (glare, alpha = 0.65; suboptimal correction, alpha = 0.66; appearance, alpha = 0.62). Test-retest reliability, assessed by the intraclass correlation coefficient was good (ICC = 0.74-0.95) except for the subscale suboptimal correction (ICC = 0.61). Almost all subscales and the overall score showed significant inter-correlations. Low to moderate correlations were found between the subscales of the NEI-RQL-42 and the NEI-VFQ-25, which measure similar constructs. The NEI-RQL-42 showed good construct validity in terms of refractive error (myopia, hyperopia and emmetropia) and mode of refractive correction (spectacles, contact lens and no correction) discrimination. Conclusion The Turkish version of the NEI-RQL-42 is a reliable and valid measure of vision-related quality of life in patients with refractive error.
Keywords: National Eye Institute Refractive Error Quality of Life Instrument (NEI-RQL-42); Validity; Reliability; Refractive error; QUESTIONNAIRE; VALIDATION; LENSES